Integrated Lesson in Teaching Oral Skill - Ila Amalia (English Education Department, 2019)
This study aimed to identify the integrated lesson as an alternative teaching strategy in pronunciation teaching. The pronunciation teaching mainly focused on word ending of past tense regular verbs. The participants of the study included a lecturer and 30 students of English education department. To collect the data, the researcher used observation and reading test. The result showed that the lecturer employed the integrated lesson based on some criteria: the students, the lecturer, the learning environment, the learning resources, and the classroom activities. The reading test result showed that from 30 students, 11 students got 100% of correctness, 3 students got 95% of correctness, 5 students got 90% of correctness, 4 students got 85% of correctness, 3 students got 80% of correctness, 2 students got 75% correctness, and 2 students got 70% of correctness. It was indicated that integrated lesson accomplished by the lecturer with careful planning and preparation could give positive influence to the students’ language comprehension and performance.